2009
DOI: 10.3171/2008.10.17676
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cerebral blood flow and cerebrovascular reactivity to acetazolamide in 162 patients with idiopathic normal-pressure hydrocephalus

Abstract: Both CBF and CVR decrease with the development of NPH, suggesting that hemodynamic ischemia may be responsible for manifestation of the symptoms. Impaired CVR and reduced CBF with the development of symptoms can be proposed as diagnostic criteria for idiopathic NPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
1
23
1
17
Order By: Relevance
“…One Class I study of 162 patients (with limited generalizability because patients were selected for surgery on the basis of a TT and CT cisternography with Table 1 Normal pressure hydrocephalus score used by a number of authors to quantify patients' limitations iodinated contrast) 24 found that SPECT cerebral blood flow (CBF) in responders was no different from CBF in controls or nonresponders. The study also found that CBF reactivity to acetazolamide was significantly impaired in responders compared with controls (p , 0.0025) and nonresponders (p , 0.005).…”
mentioning
confidence: 99%
“…One Class I study of 162 patients (with limited generalizability because patients were selected for surgery on the basis of a TT and CT cisternography with Table 1 Normal pressure hydrocephalus score used by a number of authors to quantify patients' limitations iodinated contrast) 24 found that SPECT cerebral blood flow (CBF) in responders was no different from CBF in controls or nonresponders. The study also found that CBF reactivity to acetazolamide was significantly impaired in responders compared with controls (p , 0.0025) and nonresponders (p , 0.005).…”
mentioning
confidence: 99%
“…Thus, one of our objectives was to identify a preoperative CBF estimate of prognostic value. Although several studies have not been able to find any relationship between pretreatment CBF and outcome after shunt insertion (33,34), other groups have reported different and sometimes contradictory correlations (35)(36)(37)(38). Some studies (36,38) found that patients with higher global or hemispheric preoperative CBF showed the most consistent clinical improvement after shunt therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, should a globally uniform CVR deficit be the hypothesis, as is the case in hydrocephalus (Chang et al, 2009b), the calibration issue may become more relevant. The fact that the slopes associating our resting-state CVR with standard CVR values are not uniform (Table 2) may present a challenge, raising questions such as "is this calibrationfactor variability large enough to prevent the detection of patient-control differences in CVR?".…”
Section: Practical Considerations and Limitationsmentioning
confidence: 99%